Analysis of a total hip Prosthesis Proposal by the Finite Element Method under the Conditions of ISO 7206 (Revista Cientifica Ingenio Magno, 2022)
The biomechanical analysis of a new design of total hip prosthesis was performed, using the Finite Element Method. A model whose geometric characteristics provide a better self-adjustment and bone integration was proposed. The conditions for this analysis, as well as its restrictions, were under the conditions specified in ISO 7206-4: 2010. 316L stainless steel was used for the hemiprosthesis and the UHMWPE polymer for the insert. A non-linear analysis was carried out by contact pairs and by material. For the latter, an isotropic multiline nonlinear constitutive model was considered for hardening. The results obtained were the maximum efforts and displacements that the prosthesis experienced. For the load condition, a sinusoidal force was applied at 1 Hz of 200 N (preload), to 2300 N, where the following efforts were obtained: in the hemiprosthesis, a maximum effort of 42.85 MPa, below the yield stress of the material (290 MPa), in the middle acetabular component 1.78 MPa, far from the yield of the material (23 MPa) and for the bone cement 15.96 MPa, below the yield stress (43.8 MPa). The maximum displacement was 0.053 mm below the 5 mm specified by the standard.
Keywords: bone cement, finite element method, hip, prosthesis, UHMWPE.